Ukuran Perusahaan, Good Corporate Governance, Pengungkapan Corporate Social Responsibility dan Nilai Perusahaan di Indonesia - Enggar Purnama Sari; Rizqy Fadhlina Putri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The study aims to examine the effect of firm size, god corporate governance and disclosure of corporate social responsibility on firm value in banking companies listed on the Indonesia stock exc hange in 2018-2020. Good corporate governance is a proxied by managerial ownership, instititional ownership, audit committee and independent board of commissioners. This research is a quantitative research. Determinatin of the sample obtained by 11 banking companies in the period 2018-2020 so that 33 observation data were obtained. The data used is secondary data and the data analysis technique used is multiplie linear regression by conducting a series of assumption tests to ensure the feasibility of the data. The data processing used in the study uses panel data regression using the software Eviews version 10. The results of this study indicate that company size has a negative and significant effect on firm value, good corporate governance has a negative and significant effect on firm value. However, the disclosure of corporate social responsibility has no significant effeet on firm value. Meanwhile, based on the results of the simultaneous test (F Test) it shows that all independent variables have a simultaneous test (together) and significantly effect the dependent variable.